Peran Dukungan Kelompok Sebaya terhadap Psikologis Remaja dengan Acne Vulgaris - Elizabeth Risha Murlina Lema; Rizki Fitryasari; Hanik Endang Nihayati (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the role of peer group support on the psychology of adolescents with acne vulgaris. The method used is a descriptive analysis of literature studies obtained from various national and international journal references from 2020-2021. The results showed that peer support could provide positive energy, especially for adolescents with acne vulgaris prone to feeling insecure. In conclusion, psychological peer group support can increase self-confidence, reduce anxiety levels and prevent adolescents from committing suicide due to their Acne vulgaris infection. Keywords: Acne Vulgaris, Peer Group Support, Adolescent Psychology